2019
DOI: 10.1111/clr.13409
|View full text |Cite
|
Sign up to set email alerts
|

Topographic characterization of multispecies biofilms growing on dental implant surfaces: An in vitro model

Abstract: Objectives To describe the early biofilm formation over whole dental implants with its micro‐ and macrostructure, using an in vitro multispecies biofilm model. Material and methods Six bacterial strains (Streptococcus oralis, Actinomyces naeslundii, Veillonella parvula, Fusobacterium nucleatum, Porphyromonas gingivalis, and Aggregatibacter actinomycetemcomitans) were used to develop in vitro biofilms over whole titanium implants (growth times 12, 24, 48, 72, 96, and 120 hr). The morphology of biofilms was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 49 publications
6
33
2
Order By: Relevance
“…Similarly, the CLSMs patterns described by Sanchez et al () on titanium discs, described bacterial microcolonies spread over the whole surface of the disc, with minimal differences on the bacterial deposition and distribution when different surfaces were compared. In contrast, a recent report from our research group, using a similar methodology (Bermejo et al, ) but on whole dental implants, instead of discs, demonstrated clear differences between the microcolonies deposited at the peaks of the threads from those at the valleys between the threads. It is likely that the differences in the biofilms identified in this investigation, when comparing different microsurface topographies on whole implants, represent a model closer to the clinical reality than when using discs.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Similarly, the CLSMs patterns described by Sanchez et al () on titanium discs, described bacterial microcolonies spread over the whole surface of the disc, with minimal differences on the bacterial deposition and distribution when different surfaces were compared. In contrast, a recent report from our research group, using a similar methodology (Bermejo et al, ) but on whole dental implants, instead of discs, demonstrated clear differences between the microcolonies deposited at the peaks of the threads from those at the valleys between the threads. It is likely that the differences in the biofilms identified in this investigation, when comparing different microsurface topographies on whole implants, represent a model closer to the clinical reality than when using discs.…”
Section: Discussioncontrasting
confidence: 77%
“…The biofilms were grown on the whole implant surface using the protocol previously reported by our research group (Bermejo et al, ). In brief, the obtained pure cultures of each bacterium were grown anaerobically in a brain–heart infusion (BHI) modified medium, a protein‐rich medium containing BHI (Becton, Dickinson and Company) supplemented with 2.5 g/L mucin (Oxoid), 1.0 g/L yeast extract (Oxoid), 0.1 g/L cysteine (Sigma), 2.0 g/L sodium bicarbonate (Merck), 5.0 mg/L hemin (Sigma), 1.0 mg/L menadione (Merck) and 0.25% (v/v) glutamic acid (Sigma), during 24–48 hr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that modifications of titanium implant surfaces such as acid etching and sandblasting have a significant impact on early biofilm formation (Badihi Hauslich, Sela, Steinberg, Rosen, & Kohavi, ). The findings of a recent in vitro study indicated that a significantly greater bacterial biomass grew on moderately rough implant surfaces compared with minimally rough implant surfaces and that moderately rough surfaces accumulated more bacteria and these bacteria were more pathogenic (Bermejo et al, ). In this context, development of soft tissue recessions at test implants in the present study exposing micro‐rough surfaces to the oral environment combined with insufficient self‐performed biofilm control could even be considered an increased risk for the onset of peri‐implant diseases compared with implants with a machined neck.…”
Section: Discussionmentioning
confidence: 99%
“…14 Two studies had reported their experience with biofilm formation on the implant surfaces, 1,17 which would certainly account for the relapsing infections also seen in our experience. The concept of biofilms on implant surfaces is certainly emerging with growing evidence seen in dental 24 and other titanium implants. 25 Despite the relative certainty in causal microorganisms, the intended therapy seemed to vary amongst the different studies.…”
Section: Implications For Clinical Practicementioning
confidence: 99%